Emerging infectious diseases and their impact on emergency medical services: Role of emergency and paramedic - Almutairi, Fahad Ghazi; Alaoufi, Sami Mohammed; Albahouth, Ahmed Abdulaziz A; Alotaibi, ‏Hamad Marshud; Alanazi, ‏Anood Fahad; Baurasien, ‏Bander Khalid; Alharbi, ‏Yussef Falah; Alammar, ‏Fatimah Abdullah; Almutairi, ‏Khalid Assaf; Al Otaibi, ‏Mohammed Rashed; Al-Qahtani, ‏Mohammed Faraj; Alanazi, ‏Abdulrahman Ayesh Mohammad (International journal of health sciences, 2019)
Background: Emerging infectious diseases (EIDs) pose significant threats to global health due to their potential for widespread outbreaks and severe impacts on public health systems. These diseases can emerge from zoonotic sources, environmental changes, or resistance to antibiotics. Approximately 15% of human pathogens are considered to be emerging, reflecting their critical role in public health. Aim: This review aims to evaluate the impact of emerging infectious diseases on emergency medical services, with a focus on the role of zoonotic diseases, vector-borne infections, and the application of advanced surveillance technologies in managing these threats. Methods: A comparative review of literature and data sources, including global surveillance systems and recent outbreak case studies, was conducted to assess the impact of EIDs on emergency medical services. The study also examines the effectiveness of the One Health approach and the role of advanced technologies in disease monitoring. Results: Emerging infectious diseases, including zoonotic and vector-borne infections, have significantly impacted emergency medical services by increasing the demand for urgent care and resource allocation. Advances in surveillance technologies, such as molecular diagnostics and digital platforms, have improved early detection and response capabilities.